AB1195 Our experience with anakinra treatment in a tertiary centre. (23rd January 2014) - Murias, S.; Remesal, A.; Salido, C.; Vacas, B.; Mendez, A.; Arostegui, J.I.; Merino, R.
Abstract : Background: Anakinra (ANK) is a recombinant interleukin-1 receptor antagonist currently used for treating autoinflammatory syndromes. Objectives: To describe patient characteristics and their response to ANK in a tertiary centre between 2004 and 2011. Methods: Retrospective study of 35 children treated with ANK. Demographic, clinical, analytical and genetic data were recorded. They were considered as responders when they reached analytic and clinical normalization and corticosteroids could then be discontinued. Results: The sample included 21 boys and 14 girls, aged 3 days - 13 years old. Patient characteristics and response to ANK are summarised in the table [(values are expressed as n (%), median, mean (minimum-maximum)]. Responders were older at disease onset (p=0.032) and showed a high number of neutrophils (p=0.002). Nineteen (54%) cases met the criteria for systemic-onset juvenile idiopathic arthritis (SoJIA), 10 of them responded and their median time to start treatment was 1.6 years, being 4.5 for non-responders. Sixteen (46%) children did not meet the criteria for SoJIA, and 8 responded. The median time to start ANK in this group was 0.9 years for responders and 1.1 for non-responders respectively. Genetic testing performed in 27 patients showed mutation in 14 (8 MEFV, 2 TNRFSF1A, 2 NLRP3, 1 MVK y 1 NOD2), 6 of them were responders (4 MEFV, 1 NLRP3 y 1 MVK). Conclusions: In spite of study limitations, responders were older at disease onset and showed a higher number of neutrophils. Moreover, it seems that patients with SoJIA who had the shortest time of evolution responded better than those with longer disease duration. References: The pattern of response to anti-interleukin-1 treatment distinguishes two subsets of patients with systemic-onset juvenile idiopathic arthritis. Gattorno M et al. Arthritis Rheum 2008;58:1505-15. Anakinra: a safe and effective first-line treatment in systemic onset juvenile idiopathic arthritis (SoJIA). Hedrich CM et al. Rheumatol Int 2011 Nov 15 (Epub ahead of print). Disclosure of Interest: None Declared